(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Infertility caused by reproductive pathologies plays a significant role in animal breeding and could result in massive economic losses to livestock owners. Hence, this study was designed to allocate various pathological lesions in the female reproductive tract of she-camels (Camelus dromedarius) slaughtered in Egypt and isolate the causative agents associated with those pathologies. Materials and Methods: A total of 500 genitalia of adult nonpregnant she-camels aged between 6 and 15 years old were collected from three slaughterhouses at the Giza Governorate, Egypt, from August 2017 to August 2019. The uterus, cervix, and vagina were examined pathologically and microbiologically. Results: The uteri of 152 cases (30.4%), cervices of 24 cases (4.8%), and vaginae of 20 cases (4.2%) showed pathological abnormalities. The uterine inflammatory lesions were detected in 119 cases (23.8%), and the non-inflammatory lesions were detected in 58 cases (11.6%). Pathological changes of the cervix comprised 4.8%, whereas vaginal abnormalities represented 4%. The total microbial recovery rate was 28.4%, and the isolated organisms included Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, Enterobacter cloacae, Klebsiella pneumoniae, and Pseudomonas aeruginosa, in addition to Candida albicans. Trials to isolate Brucella and Salmonella species were negative; however, virological examination revealed the isolation of bovine herpesvirus type-1 in two cases. Conclusion: Inflammatory lesions were the most prevailing pathological lesions observed along the genital tract of she-camels, and E. coli was the most prevalent isolate. The microbiological burden from the genital discharge could be of zoonotic importance to the examiner and could be a contaminant to the environment and, consequently, human. In addition, attention should be paid toward the possibility of infected she-camels to transmit such infections to farm animals in contact. J. Adv. Vet. Anim. Res., 7(4): 633-646, Dec 2020 http://doi.org/10.5455/javar.2020.g462